Sustainability-driven entrepreneurship and high-growth SMEs: how to combine Davids' and Goliaths' worlds?. (2016) - Bérard, Céline; Saleilles, Séverine
This paper aims to explore how sustainability-driven SMEs experiencing high growth can succeed in combining the best of the Davids' and Goliaths' worlds. An in-depth case study was conducted within a French SME, a pioneer in organic vegetable distribution that has succeeded in evolving from an 'idealistic David' to a 'high-growth David'. Research findings reveal two sets of key actions successfully carried out by this firm: the development of a hybrid organisation through a staff representing the skills of both Davids' and Goliaths' worlds, and of a learning organisation through exploration and exploitation. They also illustrate some challenges facing most high-growth SMEs and identify some specific tensions that can arise due to the coexistence of these two worlds, in particular value diversity within the top management team.